Study of certain Haemotological Parameter in Repeat Breeding Cows - Perumal, P.; Das, S.; Mohanty, D. N.; Barik, A. K.; Mishra, P. C. (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted on certain haematological parameters in crossbred repeat breeder cows presented at outdoor of teaching veterinary clinical complex in Odisha Veterinary College, Bhubaneswar. Blood samples were collected from 30 crossbred repeat breeder cows (Group: I) and compared with normal cyclic cows (Group: II) at the stage of estrus. The blood parameters such as TWBC (Total White Blood Cells), TRBC (Total Red Blood Cells), HBG (Haemoglobin), HCT (Haemotocrit Value), ESR (Erythrocyte sedimentation rate), TPLT (Total Platelet), MCV (Mean Corpuscular Volume), MCH (Mean Corpuscular Haemoglobin), MCHC (Mean Corpuscular Haemoglobin Concentration), RDW (Red Blood Cell Distribution Width), MPV(Mean Platelet Volume) and PDW ( Platelet Distribution Width) were investigated. The mean values for repeat breeding cows were 11.00±1.88×103 mm-3, 7.43±0.95×106 mm-3, 10.64±1.51 g dl-1, 32.78±5.71%, 08.56±1.29 mm 24 Hrs-1, 601.30±2.86x103 mm-3, 44.20±3.15 μm3, 14.45±0.81 pg, 32.82±0.82 g dl-1, 15.32±1.60%, 11.67±2.64μm3 and 1.69±0.37% respectively. The corresponding values for the control group were 11.73±1.24×103 mm-3, 8.93±1.61×106 mm-3, 11.66±2.88 g dl-1, 36.04±9.15%, 11.87±1.34 mm 24 Hrs-1, 2591.00±1.38×103 mm-3, 53.00±5.34 μm3, 17.68±1.52 pg, 32.88±1.53 g dl-1, 16.89±2.27%, 7.90±1.72 μm3 and 0.97±0.09% respectively. The TRBC, HBG, HCT, ESR, MCV, MCH, MPV, PDW values of normal cyclic cows significantly differed (p<0.05) from repeat breeder cows at oestrous stage. The TPLT count was highly significant (p<0.01) in normal cyclic cows as compared to repeat breeder cows. It was concluded that lower erythrocytic indices in the cyclic non breeding condition in crossbred cows has got to interfere in the normal conception and reproduction.